2020
DOI: 10.1080/14790718.2020.1822848
|View full text |Cite
|
Sign up to set email alerts
|

Implementing translanguaging pedagogies in an English medium instruction course

Abstract: English medium education at university level is widely used in different contexts and it poses a challenge for students who are not used to studying through the medium of English. This study was carried out in a university in the Basque Country in Spain and it focuses on a course where students who are mostly Basque-Spanish bilinguals are taught through the medium of English. The course teacher applies a flexible language policy allowing for the use of three languages in the class. The aim of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This finding echoes the research of Macaro et al (2020) in which English only instruction was the preferred pedagogy. However, research conducted in Hong Kong and Spain revealed translanguaging practices were more fully embraced in their EMI programs (Muguruza et al, 2020;Tai & Li, 2020, 2021a leading to the conclusion that there are different language ideologies in operation across these countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding echoes the research of Macaro et al (2020) in which English only instruction was the preferred pedagogy. However, research conducted in Hong Kong and Spain revealed translanguaging practices were more fully embraced in their EMI programs (Muguruza et al, 2020;Tai & Li, 2020, 2021a leading to the conclusion that there are different language ideologies in operation across these countries.…”
Section: Discussionmentioning
confidence: 99%
“…The course lecturer created a multilingual space during lecture time allowing students to incorporate the multiple languages available to them. This translanguaging opportunity was greeted by positive responses from the students involved (Muguruza et al, 2020). In contrast, another study conducted by a group of researchers on EMI teaching in one institution in China (Macaro et al, 2020) uncovered negligible use of L1 in the participant lecturers' EMI classes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most studies thus far have focused on investigating how linguistic and meta-linguistic issues impede student learning in EMI and highlighted the importance of English proficiency for both lecturers and students. This demonstrates how critical the 'E' is in successful implementation of learner-centred pedagogical EMI [9,14,44,78,116]. This is echoed by growing research in language comprehension (e.g., how linguistic and metalinguistic ability affects student learning).…”
Section: Multi-dimensionalitymentioning
confidence: 95%
“…These challenges are often externally driven and are associated with EMI lecturers' choice of pedagogical strategies and their linguistic competence to provide an inclusive and effective EMI experience. For example, many studies focused on the impact of codeswitching, translanguaging, and bi/multilingual pedagogies on students' learning and satisfaction [7,10,[44][45][46]. Studies have also provided compelling evidence regarding the multidimensionality of EMI, as seen through different kinds of assessment approaches [28], differences between content-driven and language-driven EMI [28], and lecturers' profiles, backgrounds, needs, and teaching styles [27,39,47,48].…”
Section: Learner-centred Pedagogy In He and Emimentioning
confidence: 99%
“…To further Bjorkman's (2016) argument, consideration could be given to addressing how EMI lecturers' bilingual repertoires can be developed to strengthen their EMI teaching. More recently, research has reported the role of lecturers' L1 within their EMI teaching (Lin & Lo, 2017;Muguruza et al, 2020;Sah & Li, 2022;Tai & Li, 2021). This has somewhat broken the silences around actual translanguaging practices situated within "English" Medium of Instruction.…”
Section: Research Into English Medium Instructionmentioning
confidence: 99%